2022
DOI: 10.1186/s12870-022-04006-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome and methylome analyses reveal the molecular regulation of drought stress in wild strawberry (Fragaria nilgerrensis)

Abstract: Background Fragaria nilgerrensis, which is a diploid wild strawberry with excellent drought-resistance, would provide useful candidate genes for improving drought resistance of cultivated strawberry. So far, its molecular regulatory networks involved in drought stress are unclear. We therefore investigated the drought response regulatory networks of F. nilgerrensis based on the integrated analysis of DNA methylation, transcriptome and physiological traits during four time points under drought s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…A growing body of research indicates that modifications to the levels of secondary metabolites accumulated [ 29 – 30 ] and DNA methylation status of the genome and functional genes [ 31 32 ] are essential for plant adaptation to drought stress. Uncertainty exists regarding the precise method by which DNA methylation controls plant secondary metabolism during drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research indicates that modifications to the levels of secondary metabolites accumulated [ 29 – 30 ] and DNA methylation status of the genome and functional genes [ 31 32 ] are essential for plant adaptation to drought stress. Uncertainty exists regarding the precise method by which DNA methylation controls plant secondary metabolism during drought.…”
Section: Discussionmentioning
confidence: 99%
“…Similar characteristics were shown in E. senticosus , wherein at 50% water content, the ideal level for saponin accumulation, some triterpene saponins were greatly increased, and others were significantly decreased. This is mainly because plants first produce secondary metabolic upstream chemicals with very modest molecular weights in response to water scarcity [ 31 ]. More -OH, -OCH 3, and unsaturated double bonds are present in these upstream compounds, which can directly and quickly increase the antioxidant capability of cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most eukaryotes, the frequent DNA methylation is usually occurs in the cytosine base, which contains CG, CHG and CHH (H for A, T or C) in total three types [18]. Among these three types, the CG methylation level is significantly higher than the CHG or CHH methylation types [23]. CG methylation can occur in the promoter region and part of the pre-transcriptional region, as well as in the 3' end and part of the post-transcriptional region and may inhibit gene expression.…”
Section: Characteristics Of Dna Methylation Modificationsmentioning
confidence: 99%
“…In rice, 70% of drought-induced epigenetic methylation sites are demethylated, and stress exposure during the reproductive stage leads to a negative correlation between yield and methylation rate, indicating critical crosstalk between epigenetic and reproductive signals in rice plants under drought stress [50,51]. DNA methylation in wild strawberries (Fragaria nilgerrensis) under drought stress may affect gene expression, regulating osmotic capacity and maintaining a balance between reactive oxygen species regeneration and clearance through ABA-dependent signaling pathways, thereby affecting plant drought tolerance [52]. In this study, we found that M. ruthenica genomic methylation levels decreased after two drought stress exposures, which may have triggered 'priming' stress mechanisms in the plants.…”
Section: Dna Methylation May Contribute To Plants Stress Memory Forma...mentioning
confidence: 99%